Elements of Successful Implementation of "PLAVON" (Online Services) At the Sidoarjo Regency Population and Civil Registry Service - Abdillah, Razif; Hardjati, Susi (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
Sidoarjo Dinas Kependudukan dan Catatan Sipil Online Services (Plavon) is the application of e-government practices in the field of online population administration (adminduk) services carried out by the Sidoarjo Regency Population and Civil Registry Service in an effort to provide fast and easy population services. The aim of this research is to determine the application of Plavon Dinas Kependudukan dan Catatan Sipil Sidoarjo as an online population administration service using theory from the results of a Harvard JFK School of Government study consisting of Support, Capacity, and Value. This research uses a qualitative descriptive method with data collection using literature study, interviews, and observation. Involving the Sidoarjo Dinas Kependudukan dan Catatan Sipil Office and the community as Plavon users. The results of this research show that the implementation of Plavon as an online population administration service is good even though there are still obstacles in the document upload process.